2023
DOI: 10.5435/jaaosglobal-d-22-00258
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Malleolar Fracture Assessment: An Independent Interobserver and Intraobserver Validation of Three Computed Tomography-Based Classifications

Abstract: Background: Posterior malleolus fractures occur in up to 50% of all ankle fractures. Several classification systems exist for their characterization, especially under CT. However, those classifications do not report the level of agreement or do it incompletely. This study aims to independently assess three posterior malleolus fracture classifications (Haraguchi, Bartonı ´ cek/Rammelt, and Mason). Methods: This study was designed according to the Guidelines for Reporting Reliability and Agreement Studies. Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(66 reference statements)
0
1
1
Order By: Relevance
“…Our study found that there is a correlation between the rater's experience and interobserver agreement of the Mason & Malloy classification, contrary to previous papers on this subject [17,18]. Rater no.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study found that there is a correlation between the rater's experience and interobserver agreement of the Mason & Malloy classification, contrary to previous papers on this subject [17,18]. Rater no.…”
Section: Discussioncontrasting
confidence: 99%
“…This was a study with nine raters [17]. Another paper by Morales et al also showed moderate interobserver reliability for the M&M classification with a global κ value of 0.54 (95% CI: 0.47-0.62), rated by six evaluators [18]. It is also worth mentioning a study by Kleinertz et al with four raters which presented Fleiss' κ value of 0.724 (95% CI: 0.674-0.774) [19].…”
Section: Discussionmentioning
confidence: 84%